2002
DOI: 10.1086/346199
|View full text |Cite
|
Sign up to set email alerts
|

Quiet-Sun Magnetic Fields at High Spatial Resolution

Abstract: We present spectro-polarimetric observations of Inter-Network magnetic fields at the solar disk center. A Fabry-Perot spectrometer was used to scan the two Fe I lines at λ6301.5 Å and λ6302.5 Å. High spatial resolution (0. ′′ 5) magnetograms were obtained after speckle reconstruction. The patches with magnetic fields above noise cover approximately 45 % of the observed area. Such large coverage renders a mean unsigned magnetic flux density of some 20 G (or 20 Mx cm −2 ), which exceeds all previous measurements… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 19 publications
7
67
0
Order By: Relevance
“…Unfortunately, the signals are barely above the noise level, thus it has not yet been possible to fully characterize the magnetic field vector in these regions. This has led to a long-standing controversy about the distribution of the module of the magnetic field vector in the internetwork (Domínguez Cerdeña et al 2003;Socas-Navarro & Lites 2004;Sánchez Almeida 2005;Martínez González et al 2006;Asensio Ramos et al 2007;López Ariste et al 2007;Socas-Navarro et al 2008; see also references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the signals are barely above the noise level, thus it has not yet been possible to fully characterize the magnetic field vector in these regions. This has led to a long-standing controversy about the distribution of the module of the magnetic field vector in the internetwork (Domínguez Cerdeña et al 2003;Socas-Navarro & Lites 2004;Sánchez Almeida 2005;Martínez González et al 2006;Asensio Ramos et al 2007;López Ariste et al 2007;Socas-Navarro et al 2008; see also references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Steiner 2003). Analyses based on visible lines suggest that the internetwork contains a sizeable fraction of fields in the kG range (Grossmann-Doerth et al 1996;Sánchez Almeida & Lites 2000;Socas-Navarro & Sánchez Almeida 2002;Domínguez Cerdeña et al 2003; but see Lites 2002). Analyses based on infrared spectral lines, on the contrary, indicate that strong fields are very rare and that weak fields dominate the PDF (Lin 1995;Khomenko et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Viticchié et al (2009) studied their association with G-band bright points and used the SIR (Stokes inversions based on response function) approach (Ruiz Cobo & del Toro Iniesta 1992) to determine that their temporal evolution is related to the filling factor rather than to the magnetic field strength. Observations with high polarimetric sensitivity revealed that magnetic fields occupy approximately 45 % of the area in internetwork patches, predominantly in intergranular spaces (Domínguez Cerdeña et al 2003). Scrutinizing the intricate fine structure of granules, Steiner et al (2010) found evidence for horizontally oriented vortex tubes, i.e., striations with leading bright rim and a trailing dark edge, which migrate in unison from the periphery to the granule's interior.…”
Section: Science With Imaging Spectropolarimetersmentioning
confidence: 99%